1986
DOI: 10.1530/acta.0.1110321
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid growth-stimulating immunoglobulins in goitrous disease: relationship to thyroid-stimulating immunoglobulins

Abstract: Thyroid growth stimulating immunoglobulins (TGI) were assayed in IgG concentrates prepared from human plasma using a cytochemical bioassay (CBA) based on the measurement of changes in glucose-6-phosphate dehydrogenase (G6PD) activity in guinea pig thyroid follicular cells. TGI was present in all 8 patients studied who had goitrous Graves' disease, in 9 who had toxic diffuse goitres with asymmetric uptake on scintigram and/or symptomatic ophthalmopathy and in 4:8 who had toxic uninodular goitre with autonomousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…Previous authors reported the presence of TGSAb in Graves' patients, and in several instances these antibodies could be detected in IgG preparations devoid of thyroid adenylate cyclase stimulatory activity (Drexhage et al, 1980;Chiovato et al, 1983;Valente er al., 1983a;Smyth et al, 1986). The discrepancy with our data could be attributed to the use of independent assays for the measurement of the two activities, although other explanations such as selection of patients can not be excluded.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Previous authors reported the presence of TGSAb in Graves' patients, and in several instances these antibodies could be detected in IgG preparations devoid of thyroid adenylate cyclase stimulatory activity (Drexhage et al, 1980;Chiovato et al, 1983;Valente er al., 1983a;Smyth et al, 1986). The discrepancy with our data could be attributed to the use of independent assays for the measurement of the two activities, although other explanations such as selection of patients can not be excluded.…”
Section: Discussioncontrasting
confidence: 93%
“…Autoantibodies able to stimulate thyroid growth (TGSAb) have been described in the serum of goitrous patients with Graves' disease or Hashimoto's thyroiditis as well as in patients with goitre not associated with the usual features of thyroid autoimmunity, such as sporadic and endemic goitre (Drexhage et al, 1980;Chiovato et al, 1983;Valente et al, 1983a;Ealey et al, 1985;Medeiros-Net0 er al., 1986;Smyth et al, 1986). The relationship between these antibodies and the thyroid adenylate cyclase-stimulating antibodies (TSAb) of Graves' disease is a matter of controversy.…”
Section: Et Almentioning
confidence: 99%
“…In hyperthyroid Graves' disease the presence of TKAb has been reported in varying frequencies from about 50% [l 11 to 100Y0 161 with most frequencies around 90% [5,7,[13][14][15][16]. but also with somewhat lower values (10,12,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%